2013
DOI: 10.1155/2013/591751
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Insulin Incorporated Nanoparticles for Oral Administration

Abstract: The current study was designed to prepare and characterize insulin incorporated nanoparticles by complex coacervation process followed by antidiabetic study of orally administered insulin incorporated nanoparticles in diabetic rats. The nanoparticles were characterized for particle size, loading and entrapment efficiency as well as in vitro release of incorporated insulin. The prepared nanoparticles were found to have an average particle size of 551.67 nm ±45.5. The highest entrapment efficiency and loading ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Area under the curves (AUC) determined from the concentration versus time plot using the linear trapezoidal method. Relative bio availabilities were calculated by the following formula using the AUC of orally fed insulin solution, insulin‐loaded core–shell nano‐particles and subcutaneous (SC) injection of insulin along with their respective doses Relative bioavailability (RA)=AUC (Oral)×Dose (Sc)AUC (Sc) ×Dose (Oral)×100 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Area under the curves (AUC) determined from the concentration versus time plot using the linear trapezoidal method. Relative bio availabilities were calculated by the following formula using the AUC of orally fed insulin solution, insulin‐loaded core–shell nano‐particles and subcutaneous (SC) injection of insulin along with their respective doses Relative bioavailability (RA)=AUC (Oral)×Dose (Sc)AUC (Sc) ×Dose (Oral)×100 …”
Section: Methodsmentioning
confidence: 99%
“…Insulin is one of the essential drugs which was massively explored to deliver through oral route in the recent past . Insulin is a protein, composed of two polypeptide chains of 21 and 30 amino acid residues joined by two disulfide bridges .…”
Section: Introductionmentioning
confidence: 99%
“…For mucoadhesion analysis of chitosan-coated NPs versus uncoated PLGA NPs, energetic and geometric stability of the polymer-mucin molecular complexes were determined using static lattice atomistic simulations (molecular mechanics simulations; Chemlite30, Hypercube Inc., Gainesville, FL, USA). The structures of PLGA and PEG were generated as natural bond angles while the ones of chitosan and glycosylated mucin (MUC) were generated using the saccharide building and sequence editor tools, respectively [34]. The individual molecules (PLGA, PEG, chitosan, and MUC) as well as the molecular complexes (PLGA-MUC and chitosan/PEG-MUC) were energy minimized and optimized using MM+ Force Field algorithm.…”
Section: In Silico Mucoadhesion Analysismentioning
confidence: 99%
“…Oral bioavailability was found to be less than 50% but the pharmacological effects of insulin have been noticed for a longer period of time with the nanoparticle as compared to parenteral insulin administration. They concluded that 10 IU/Kg of orally administered insulin given to diabetic rats which is incorporated in nanoparticles shows a maximum change in glucose level of at a time period of 5 hours [ 30 ].…”
Section: Oral Delivery Of Insulinmentioning
confidence: 99%